2005
DOI: 10.1007/s10519-005-2792-4
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Effect of the Polymorphic CGG Repeat in the FMR1 Gene on Cognitive Performance

Abstract: A CGG repeat sequence located in the 5' untranslated region of the FMR1 gene is polymorphic with respect to size and stability of the repeat during parent-offspring transmission. When expanded to over 200 repeats, the gene is hypermethylated and silenced, leading to fragile X syndrome (FXS). Recently, alleles with large unmethylated repeat tracts (premutations) have been associated with ovarian failure and a late-onset tremor/ataxia syndrome, symptoms unrelated to FXS. To further investigate the phenotype cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 44 publications
6
43
0
Order By: Relevance
“…Nevertheless, there is substantial within-syndrome variability in the severity of affectedness, as well as in the precise profile of impairments and psychopathology manifested [Mazzocco, 2000;Kaufmann, 2002;Loesch et al, 2004]. Moreover, there is emerging evidence that even the FMR1 premutation is associated with a distinctive phenotype [Johnston et al, 2001;Aziz et al, 2003;Goodlin-Jones et al, 2004;Moore et al, 2004;Allen et al, 2005;Hessl et al, 2005]. In the next sections, we briefly review those aspects of the phenotype and its variable manifestations that are relevant for understanding the language difficulties of this population.…”
Section: Implications Of the Behavioral Phenotype For Language Learnimentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, there is substantial within-syndrome variability in the severity of affectedness, as well as in the precise profile of impairments and psychopathology manifested [Mazzocco, 2000;Kaufmann, 2002;Loesch et al, 2004]. Moreover, there is emerging evidence that even the FMR1 premutation is associated with a distinctive phenotype [Johnston et al, 2001;Aziz et al, 2003;Goodlin-Jones et al, 2004;Moore et al, 2004;Allen et al, 2005;Hessl et al, 2005]. In the next sections, we briefly review those aspects of the phenotype and its variable manifestations that are relevant for understanding the language difficulties of this population.…”
Section: Implications Of the Behavioral Phenotype For Language Learnimentioning
confidence: 99%
“…Females with the premutation, especially those with larger expansions, are at an elevated risk of depression, obsessive-compulsive disorder, anxiety, and ASD [Goodlin-Jones et al, 2004;Hessl et al, 2005]. The evidence for a cognitive phenotype in premutation females, however, is more equivocal [Steyaert et al, 2003;Moore et al, 2004;Allen et al, 2005]. In large measure, the premutation phenotype results from lower FMRP levels and elevated levels of FMR1 messenger RNA [Allen et al, 2005].…”
Section: Within-syndrome Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The protocols and consent forms for ascertainment were approved by the Institutional Review Board at Emory University. For more information on study population ascertainment, see Allen et al (2005).…”
Section: Study Populationmentioning
confidence: 99%
“…In 2005 we published a study examining cognition among 66 men and 217 women with varying FMR1 repeat lengths (Allen et al 2005). We reported that women who were carriers of premutation alleles had significantly lower verbal IQ scores compared to non-carriers.…”
Section: Introductionmentioning
confidence: 99%